PERAN PENYULUH PERTANIAN DALAM MENINGKATKAN KAPASITAS PETANI PADI SAWAH DI KELURAHAN BARUGA KECAMATAN BARUGA KOTA KENDARI - Muhammad Febriansyah; Yani Taufik; Salahuddin Salahuddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
As a predominantly agrarian nation with a pivotal function in rice production, Indonesia is confronted with the challenges of enhancing productivity and ensuring food security. It is therefore essential to strengthen the role of agricultural extension workers as agents of change in order to enhance farmers' capacity, which is currently suboptimal, particularly in Baruga Village, due to low technology adoption, limited knowledge, and insufficient extension support. The present study was designed using a quantitative approach with a survey research design. The study population consists of all paddy farmers in Baruga Village, totalling 280 individuals. The sample size was determined using the Slovin formula, which resulted in a sample size of 73 respondents. The selection of the samples was conducted through the utilisation of a simple random sampling method. The data was collected through several methods, including surveys, interviews, a literature review, and documentation. The research variables were the role of agricultural extension workers and the capacity of irrigated rice farmers. The analysis was conducted using a quantitative descriptive approach. The findings of the study suggest that the function of agricultural extension workers in Baruga Village, Baruga Subdistrict, Kendari City, remains in the low category whether as educators, motivators, or facilitators and thus has not been optimal in supporting the enhancement of irrigated rice farmers' capacity. Conversely, farmers' capacity is predominantly in the moderate category, signifying that farmers possess fundamental farming skills but are not yet equipped to fully implement technical, managerial, adaptive, and partnership aspects. This situation indicates a correlation between the limited role of extension workers and the suboptimal capacity of farmers; therefore, a more intensive, systematic, and sustainable strengthening of the extension workers' role is necessary to improve the performance and productivity of irrigated rice farming.